Life without light : a journey to Earth's dark ecosystems - Stewart, Melissa (New York : Franklin Watts, 1999)
Explores some of the world's most unusual ecosystems found in caves, the deep sea, hydrothermal vents on the ocean floor, underground aquifers, and rock deep below earth's surface.
Includes bibliographical references (p. 123-124) and index.
Booklist.
Books for the Teen Age (NYPL).
School Library Journal.
Young Adult
Keywords: Biotic communities -- Juvenile literature; Habitat (Ecology) -- Juvenile literature; Life (Biology) -- Juvenile literature; Life -- Origin -- Juvenile literature; Biotic communities; Habitat (Ecology); Life (Biology); Life -- Origin; Animals -- Habitations; Biotic communities; Life (Biology); Life -- Origin